PENERAPAN MODEL PEMBELAJARAN CTL DENGAN MEDIA PEMANFAATAN SUMBER DAYA ALAM UNTUK MENINGKATKAN KESADARAN LINGKUNGAN DAN PRESTASI BELAJAR IPS SISWA KELAS VII A SMP AL-ISLAM I SURAKARTA - S., Sutarmi; Joebagio, Hermanu; Suryani, Nunuk (Sebelas Maret University (UNS), 2014)
The objective of research was to find out: (1) the Social Science learning process of Contextual Teaching And Learning with natural resource utilization media inthe 7thA graders of SMP Al-Islam I Surakarta, (2) whetherÂ or not the application of Contextual Teaching and Learning model with Natural ResourceUtilization Media to improve Environmental Awareness in the 7thA graders of SMP Al-Islam I Surakarta, and (3) whether or not the application of Contextual Teaching and Learning model with Natural Resource Utilization Media to improve the Learning Achievement of Social Science in the 7thA graders of SMP Al-Islam I Surakarta.This research was taken place in classroom action research method in three cycles. The subject of research was the 7thA graders of SMP Al-Islam I Surakarta. The object of research was teaching-learning process including student creativity and activity in teaching-learning processactivity, student environment and learning achievement.The result of research showed that the implementation of social science learning with Natural Resource Utilization Media the 7thA graders of SMP Al-Islam I Surakarta conducted in three cycles could (1) improve student activeness, make the teaching-learning activity run smoothly, cheerfully, seriously and joyfully. The students who were formerly lazy and asking question hesitantly because of their less self-confidence asked question bravely and came to the front to make presentation. It could be seen from the activity score improving in each cycle from 11.36% to 14.96% and finally to 16.64%. (2) The studentsâ€™ environmental awareness taken from the data of questionnaire improved from pre-cycle with the score of79.82% to 80.39% in cycle I, to 84.14% in cycle II, and to 85.25% in cycle III. (3) This learning model could improve the studentsâ€™ learning achievement, as indicated by the score reaching KKM of 28.57% in prior condition increasing to 57.14% in cycle I, to 71.43% in cycle II, and to 89.29% in cycle III.